2020
DOI: 10.1038/s41368-020-00107-z
|View full text |Cite
|
Sign up to set email alerts
|

Titanium mesh for bone augmentation in oral implantology: current application and progress

Abstract: Guided bone regeneration (GBR) is an effective and simple method for bone augmentation, which is often used to reconstruct the alveolar ridge when the bone defect occurs in the implant area. Titanium mesh has expanded the indications of GBR technology due to its excellent mechanical properties and biocompatibility, so that the GBR technology can be used to repair alveolar ridges with larger bone defects, and can obtain excellent and stable bone augmentation results. Currently, GBR with titanium mesh has variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
126
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 82 publications
(140 reference statements)
2
126
0
Order By: Relevance
“…Recent research has identified a role of metallic ions, such as magnesium (Mg), strontium (Sr), zinc (Zn) and silicon (Si) in the maintenance of bone and stimulation of osteogenesis [11]. In the dental field, the use of nickel-titanium materials for bone regeneration has been explored due to their numerous desirable properties, including good mechanical strength, good biocompatibility, corrosion resistance and elastic modulus (Table 2) [163]. Studies have found that using a nickel-titanium membrane with pore sizes between 50 and 125 µm has resulted in vascularization and bone healing.…”
Section: Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has identified a role of metallic ions, such as magnesium (Mg), strontium (Sr), zinc (Zn) and silicon (Si) in the maintenance of bone and stimulation of osteogenesis [11]. In the dental field, the use of nickel-titanium materials for bone regeneration has been explored due to their numerous desirable properties, including good mechanical strength, good biocompatibility, corrosion resistance and elastic modulus (Table 2) [163]. Studies have found that using a nickel-titanium membrane with pore sizes between 50 and 125 µm has resulted in vascularization and bone healing.…”
Section: Metalsmentioning
confidence: 99%
“…The major drawbacks of using nickel-titanium membranes include the need for a second surgical procedure and the possibility of soft tissue dehiscence and exposure of the membrane [164]. Over the years, titanium membranes have been used in bone reconstruction in alveolar bone defect sites; to stabilize the placement of autograft materials; as an adjunct for other grafting materials and as a membrane barrier for GBR (Table 2) [163].…”
Section: Metalsmentioning
confidence: 99%
“…Pore size of the barrier membrane in the GBR influences the invagination of soft tissue and the penetration of oxygen, nourishment, and fluid required for osteogenesis. [10][11][12]39] The channels of the HC scaffolds can be considered as pores of the barrier membrane.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that when vertical ridge augmentation is performed, the risk of exposure of the titanium mesh is high [38][39][40] . Early exposure of the bone graft to the oral cavity and exposure occurring within 4 weeks after bone augmentation have been identi ed as reasons for infection and bone graft loss, and the soft tissue associated with in ammation remains in place and impedes the ingrowth of bone even after the resolution of the in ammation 17,41 . However, other studies have reported that premature exposure to titanium mesh did not result in either infection or decreased bone augmentation 19,42 .…”
Section: Discussionmentioning
confidence: 99%